Penafsiran Imam Nawawi al-Bantani Tentang Jin (Kajian Tematik dalam TafsÄ«r MarÄh LabÄ«d) - M Amin Mubarok; Didi Junaedi; M. Maimun (UIN Siber Syekh Nurjati Cirebon, 2016)
All religiouns believe in the existency of the spirit of jin. Long before the existency of Islam, religiouns like Majusi, Yahudi, and Christiany too believe in the existency of the jin. Based on the above believe the mayority of muslim and non muslim will believe the existency named jin. But minority of muslim like of the filosof and a part of muâ€™tazilah wish the existency of the spiritual creature named jin.Â After all, the term jin is always meantioned in the Holy Qurâ€™an. The above meationed term erouse many debate to fine out the actual meaning and to understand accureatly . based on the aboveÂ fenomenal the writer feels attracted to investigate the meaning of jin in the al-Qurâ€™an and to compare the translition of the word jin found in tafsir marÄh labÄ«d cretion of Imam Nawawi al-Bantani. By understanding the cretion of Imam Nawawi al-Bantani, it is expected to give the meaning of jin more preacisely and to understandÂ the translition implemented by Imam Nawawi al-Bantani about the jin especially when compared with the present. Keyword: Jin, Tafsir MarÄh LabÄ«d, al-Qurâ€™an